2015
DOI: 10.5812/jjm.26990
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of mRNA Expression Levels of cyp51A and mdr1, Candidate Genes for Voriconazole Resistance in Aspergillus flavus

Abstract: Background:Voriconazole Resistance (VRC-R) in Aspergillus flavus isolates impacts the management of aspergillosis, since azoles are the first choice for prophylaxis and therapy. However, to the best of our knowledge, the mechanisms underlying voriconazole resistance are poorly understood.Objectives:The present study was designed to evaluate mRNA expression levels of cyp51A and mdr1 genes in voriconazole resistant A. flavus by a Real-Time Reverse Transcriptase Polymerase Chain Reaction (RT-PCR) technique.Materi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Great variability in expression patterns was also described in studies focusing on other species of the genus, thus providing controversial results. Specifically, in A. flavus, cyp51 transcript levels were not correlated to VRC-resistant phenotypes in a study (30), whereas 80% of non-wt strains displayed cyp51A overexpression in another one (31), although in the latter work resistance was linked to multidrug efflux pump overexpression as well.…”
Section: Discussionmentioning
confidence: 91%
“…Great variability in expression patterns was also described in studies focusing on other species of the genus, thus providing controversial results. Specifically, in A. flavus, cyp51 transcript levels were not correlated to VRC-resistant phenotypes in a study (30), whereas 80% of non-wt strains displayed cyp51A overexpression in another one (31), although in the latter work resistance was linked to multidrug efflux pump overexpression as well.…”
Section: Discussionmentioning
confidence: 91%
“…Azole resistance mechanisms in clinical A. fumigatus isolates have been investigated extensively, and the main mechanism is the presence of point mutations in the target gene cyp51A (4,5,22,23). In contrast to A. fumigatus, the resistance mechanisms of A. flavus have been examined in a limited number of clinical strains (15,20,21,24). Liu et al (25) suggested that a T788G (S240A) missense mutation in cyp51C conferred voriconazole resistance on A. flavus isolates.…”
mentioning
confidence: 99%
“…To date, three studies investigated the overexpression of target or efflux pump genes in clinical isolates of A. flavus (20,21,24). In a study, four of five voriconazole non-WT isolates had cyp51A and MDR1 overexpression (24), while in the other study, one of three non-WT isolates exhibited overexpression of target genes (cyp51A, cyp51B, and cyp51C) and efflux pump genes (MDR1, MDR2, atrF, and mfs1) (20). In a study by Paul et al (21), two non-WT isolates showed voriconazole-induced overexpression of Cdr1, suggesting a possible role of multidrug efflux pumps.…”
mentioning
confidence: 99%
“…Consequently, in the last few years molecular mechanisms underlying azole resistance in A. fumigatus strains have been thoroughly investigated with regard to either point mutation(s) or overexpression of the target gene of azoles (cyp51A) and non-cyp51-mediated resistance (11). In contrast to the case with A. fumigatus, in the last 5 years only a few sporadic reports documenting VRC-resistant A. flavus (VRC-RAfla) isolates have been recorded (13)(14)(15)(16)(17). Also, the true burden of azole resistance in A.…”
mentioning
confidence: 99%
“…Unlike for other Aspergillus species, which possess two cyp51 proteins, i.e., cyp51A, and cyp51B, in A. flavus, three cyp51 proteins are found: cyp51A, cyp51B, and cyp51C. So far, limited studies (Ͻ10) analyzing the genetic changes and/or overexpression of azole target genes, i.e., cyp51A and cyp51C, and efflux pump (EP) genes causing decreases in intracellular drug concentrations in laboratory-generated or clinical isolates of azole-resistant A. flavus have been described (13)(14)(15)(16)(17)(18)(19). Krishnan-Natesan et al (19) demonstrated the role of cyp51A mutations in VRC-resistant laboratory-generated A. flavus strains, whereas in two recent studies, mutations in the cyp51C gene in clinical azole-resistant A. flavus strains were reported (13,15).…”
mentioning
confidence: 99%